2020
DOI: 10.1186/s12885-020-07414-y
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic characterization of aggressive breast cancer cells exhibiting invasive phenotype: impact of non-cytotoxic doses of 2-DG on diminishing invasiveness

Abstract: Background Metabolic reprogramming is being recognized as a fundamental hallmark of cancer, and efforts to identify drugs that can target cancer metabolism are underway. In this study, we used human breast cancer (BC) cell lines and established their invading phenotype (INV) collected from transwell inserts to compare metabolome differences and evaluate prognostic significance of the metabolome in aggressive BC invasiveness. Methods The invasiveness of seven human BC cell lines were compared using the transw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Several previous reports have demonstrated similar effects of 2-DG on breast cancer cells, with reduction in their migration [ 40 ] and proliferation [ 41 45 ]. In another recent report, enhanced glucose uptake was correlated with enhanced invasiveness of several breast cancer cell lines, whereas low doses of 2-DG (1 mM) significantly reduced their invasive capacity [ 46 ]. Our data is consistent with these reports, in the same concentration range (0.5–1 mM).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous reports have demonstrated similar effects of 2-DG on breast cancer cells, with reduction in their migration [ 40 ] and proliferation [ 41 45 ]. In another recent report, enhanced glucose uptake was correlated with enhanced invasiveness of several breast cancer cell lines, whereas low doses of 2-DG (1 mM) significantly reduced their invasive capacity [ 46 ]. Our data is consistent with these reports, in the same concentration range (0.5–1 mM).…”
Section: Discussionmentioning
confidence: 99%
“…For example, 1 mM 2-DG blocked cell viability and induced cytotoxicity in liver cancer cells HepG2 in this study. It has been reported that 1 mM 2-DG is toxic in breast cancer cell SUM149 [ 48 ], but it is not toxic in other breast cancer cells MDA-MB-231, HCC1937, HDQ-P1, and MCF-7 cells [ 48 , 49 ]. Thus, the findings from this study can be referenced in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence labeling and image acquisition were performed as described previously, with some modifications. 29 Briefly, cells were fixed with 4% paraformaldehyde in phosphate-buffered saline (PBS; Nissui Pharmaceutical Co., Ltd.; Tokyo, Japan) for 15 min, and given three washes with PBS. Cells were then blocked with PBS containing 5% fetal calf serum and 0.3% Triton ×100, followed by incubation with primary antibody for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%